+0  
 
0
131
2
avatar+253 

Thanks in dac

Veteran  May 25, 2017
Sort: 

2+0 Answers

 #1
avatar
0

Possible derivation:
d/dx(tan^(-1)(sin(5 x)))
Using the chain rule, d/dx(tan^(-1)(sin(5 x))) = ( dtan^(-1)(u))/( du) ( du)/( dx), where u = sin(5 x) and ( d)/( du)(tan^(-1)(u)) = 1/(1 + u^2):
 = (d/dx(sin(5 x)))/(1 + sin^2(5 x))
Using the chain rule, d/dx(sin(5 x)) = ( dsin(u))/( du) ( du)/( dx), where u = 5 x and ( d)/( du)(sin(u)) = cos(u):
 = cos(5 x) d/dx(5 x)/(1 + sin(5 x)^2)
Factor out constants:
 = (5 d/dx(x) cos(5 x))/(1 + sin^2(5 x))
The derivative of x is 1:
Answer: | = (15 cos(5x)) / (1 + sin^2(5x))

Guest May 25, 2017
 #2
avatar+77068 
+1

 

 

Note  .......derivative of arctan (u)  =   1 / ( 1 + u^2) * du  .....so......

 

f(x)  =   arctan (sin (5x))   =   [  1 /  [ 1 + (sin(5x) )^2]  * 5 cos (5x)  =

 

[ 5 cos (5x) ]  /  [ 1 + sin2(5x) ]

 

 

cool cool cool

CPhill  May 25, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details